Optimization of The Mechanical Drive on Set-up of Homemade Surface Plasmon Resonance - Muhammad Arifin; Febrilian Dwi Laksono; Supardianningsih Supardianningsih; Kamsul Abraha (Universitas Sebelas Maret, 2017)
Mechanical optimization has been done on the surface plasmon resonance (SPR) homemade. At set-up, angle scanning comes a small resolution to detect changes in the thickness of the thin film or refractive index of the sample. The mechanical drive has a function to rotate the prism and detector. Torsional Spring-Loaded Gear Antibacklash is used to improve the accuracy of the mechanical drive. The stepper motor is used to rotate the mechanical drive automatically. The built system has successfully increased the resolution of the prism rotation angle by 0.01°. The test using the blank prism indicates the angle of Total Internal Reflection occurs at an incident angle of 41.80 °. The SPR phenomenon was observed in a thin layer of gold deposited on the prism using a vacuum evaporator. The observed SPR angles on samples A, B, C, D, E, F, G, H and I were 45.02°, 45.05°, 46.30°, 44.48°, 44.70°, 45.49°, 45.52°, 45.66°, and 44.44°, respectively. The SPR angle change shows the difference in the thickness of the gold thin film.